Professional Foreign Language as a Means of Increasing the Competitiveness of the Future Specialist - Bohatyrets, Valentyna; Tsikhotska, Olga; Horbach, Oksana; Buzdugan, Olena; Serebrianska, Irina (ALRJournal. 2020; 4(9): 190-199 |, 2020)
The purpose of the article: to analyze the training of modern specialists in foreign languages as a means of increasing their competitiveness and professional mobility. In the study, we will consider the dependence of teaching methods for successful application in everyday life. Based on the content analysis of websites, which contains a list of vacancies and resumes of specialists in various fields, and statistical data processing, conclusions were made on the need to master a professional foreign language at the appropriate level of future professionals. The study grounds the concept of intercultural professional communication and the competence approach to the formation of a competitive specialist. It determines the level of professionalism of specialists in the context of foreign language skills. The study is based on the content analysis of the Work.ua website, which contains a list of vacancies and resumes of specialists in various fields and statistical data processing. A lot of conclusions were drawn on the relationship between the regional labor market, competitiveness and professionalism in foreign languages. This article draws the following important conclusions: it is necessary to study a foreign language consistently and systematically; there is also a need to have both communication skills and grammar skills and knowledge for effective communication in foreign languages; the profession affects the level of knowledge of foreign languages and therefore the profession determines the level of competitiveness of the specialist; for more prestigious professions due to the needs of the labor market is characterized by a higher level of salaries, a higher level of knowledge of foreign languages. The level of professionalism determines the competitiveness of the specialist.
Keywords: professional foreign language; specialist competitiveness; labor market needs; knowledge of foreign languages